Reflections on an Architectural Manifesto Daniel Solomon and the Search for Humane Housing (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Daniel Solomon is one of the great practitioners of humane housing design in the world today. His book amounts to a manifesto of sorts, though it is far from a systematic statement; it is, rather, partly biography, partly urban history and partly philosophy in a way that evokes the messy reality of and utopian hopes for great cities Solomon is reaching for his star, and that fact that he often comes up short in terms of social theory takes away nothing from the sense of an honorable quest by a great architect and fine human being.